(untitled) (Journal of Management and Business Education, 2026)
This action-research examines a four-week flipped-classroom intervention in an Intermediate Accounting course at a Bangladeshi government women’s college. 62 of 73 enrolled second-year Bachelor of Business Administration (BBA) students participated in the intervention; participation and formative data were collected across four weeks using short pre-class videos (YouTube), a closed Facebook group, and weekly Google-Form formative quizzes. Engagement indicators such as average video views, class attendance, and mean quiz scores increased during the intervention. A paired‑samples t‑test indicated a statistically significant within‑student improvement, t(27) = 8.31, p < .001, Cohen’s d = 1.57, with a 95% confidence interval for the mean difference of [8.53, 14.12]. A Wilcoxon signed‑rank test produced consistent results. Because the study employed a practitioner‑led action‑research design without a control group, the results should be interpreted as exploratory evidence associated with the flipped intervention rather than causal proof of effectiveness. Reflections from students indicate that pre-class preparation, peer collaboration, and flexible access to educational materials contributed to increased participation. The study shows how low-cost digital platforms can facilitate blended learning methods in higher education environments with limited resources. However, further research using comparative or longitudinal methods is needed for a more comprehensive assessment of learning outcomes and sustainability.